The effect of humour and mood on memory recall - Tunku Badli, Tunku Saraa Zawyah; Dzulkifli, Mariam Adawiah (Elsevier, 2013)
The research presented here attempted to investigate the effect of humour on memory recall, while taking into consideration the mood of the participants. Participants were divided into two groups; neutral and dysphoric group. Both groups viewed humorous video clips which included displayed words and were asked to recall as many words from the videos. Findings showed that both groups had higher recall of words. Thus, the enhanced memory due to humour or humour effect can occur not only to individuals in a neutral mood, but also those in dysphoric mood.